Food supply and economic development : with special reference to Egypt - Amin, Galal A. (London : Frank Cass & Co Ltd., 1966)
This volume is based on the on authors thesis, University of London. It is aimed at investigating the role played by food supply in economic development and to examine the food problem in the United Arab Republic of Egypt.
Includes bibliographical references.
lje 25/1/19
Loans
Keywords: Food supply; Economic development; Egypt